A case report of Omenn syndrome in siblings - Berendt, Agnieszka; Wójtowicz-Marzec, Monika; Dobrowolska, Monika; Kwaśniewska, Anna (Journal of Education, Health and Sport, 2019)
The article describes a case of Omenn syndrome in neonatal period. Omenn syndrome was diagnosed in two of three children of the same parents. Both of children had skin erythroderma since birth and eosynophilia in blood tests. The course of the disease in both cases was fatal. Condition has inborn character and autosomal recessive pattern of inheritance. Around third month of life first symptoms of the disease appear: chronic diarrhea, failure to thrive, severe infections, hepatosplenomegaly, erythroderma, loss of hair. Marrow bone transplantation or cord blood stem cell transplantation is the only treatment. Diagnosis of Omenn syndrome is difficult because of incomplete clinical picture of the disease in newborn period, rarity of disease and skin changes similar to those in ichtiosis, histiocytosis, other SCID or atopic eczema. It is particularly important to be vigilant in case of skin changes such as severe erythroderma and skin desquamation accompanied by abnormalities in blood tests. Such patients should be referred to hematological centers. Vaccination with attenuated vaccines should be postponed. Detailed laboratory tests in Omenn syndrome reveal low level of IgG, IgA, IgM and elevated level of IgE, absence of B-cell clones and abnormal amount of T-cell clones. Families burden with severe combined immunodeficiency disease (SCID) require genetic counseling. Families affected by Omenn syndrome or RAG-dependent SCID could benefit from prenatal diagnosis by detection of RAG genes mutations of fetal samples by direct sequencing.